Investment Strategies: Financial Metrics, Governance, and Inflation in IDX Consumer Goods Firms - Christina Juliana; Natasya Kristian; Thio Anastasia Petronila (Jurnal Ekonomi, 2026)
This study examines how financial factors, corporate governance (GCG), and inflation affect managerial investment decisions in IDX-listed consumer goods companies. Financial variables include the Tax-to-Book Ratio and Net Profit Margin, while corporate governance factors comprise Independent Commissioners and the frequency of Board of Directors meetings with the Audit Committee. The study analyzes 39 companies (156 sample units) from 2020 to 2023 using the Structural Equation Modeling (SEM) method with Partial Least Squares (PLS). Findings reveal that financial and corporate governance variables significantly influence investment decisions, whereas inflation has no significant impact.